2021
DOI: 10.1039/d0nr07681c
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell gold nanorod@mesoporous-MOF heterostructures for combinational phototherapy

Abstract: A core–shell heterostructure consisting of plasmonic gold nanorods and porphyrinic metal–organic frameworks is synthesized as a promising platform to combine photodynamic therapy and photothermal therapy for enhanced tumor treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…The redshift was attributed to the enlarged conjugated area of porphyrin after the formation of the PCN-224, which was in accordance to the reported literature. [43] Importantly, CaO PCN-224-CaO 2 -HA was found to accumulate effectively at the tumor site after 12 h of intravenous administration, which was attributed to the enhanced permeability and retention effect 44 and HA mediated targeting accumulation of the therapeutic agent (Fig. 6a and 6b).…”
Section: Resultsmentioning
confidence: 94%
“…The redshift was attributed to the enlarged conjugated area of porphyrin after the formation of the PCN-224, which was in accordance to the reported literature. [43] Importantly, CaO PCN-224-CaO 2 -HA was found to accumulate effectively at the tumor site after 12 h of intravenous administration, which was attributed to the enhanced permeability and retention effect 44 and HA mediated targeting accumulation of the therapeutic agent (Fig. 6a and 6b).…”
Section: Resultsmentioning
confidence: 94%
“…9d). 143 The porphyrin MOF is composed of Zr 4+ and TCPP. The TEM image showed that the AuNRs are surrounded by spindle MOFs, forming a core-shell heterostructure with an average size of about 102.7 Â 186.8 nm.…”
Section: Pdt-based Combination Therapymentioning
confidence: 99%
“…The PTT mechanism works by increasing tumor micro‐environment temperature by exploiting GNP's light to heat conversion properties which induce apoptosis and/or necrosis of the tumor cells. Several gold nanostructures such as gold nanorod, [ 271 ] nanocages, [ 272 ] nanostars, [ 273 ] nanoshells [ 274 ] were reported to be effective for PTT mediated cancer therapy. Gold shell nanoparticles (GS‐NPs), which are made up of a silica core and a gold shell with a diameter of about 150 nm, can absorb light in the near‐infrared (NIR) range and then convert the photon energy to heat.…”
Section: Gnps Based Improved Therapeuticsmentioning
confidence: 99%